Traces Of Mysticism In ibn Sina’s Thought - Dani Ramdani; Amsal Bakhtiar (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2025)
This article aims to analyze the dimension of mysticism in Ibn Sina’s system of thought-an Islamic rationalist thinker who in several of his works shows deep spiritual-mystical tendencies. Using the approach of falsafi Sufism and a qualitative method based on literature study, this article examines major works such as Al-Isharat wa al-Tanbihat, Hayy Ibn Yaqzan, Risalah fi Mahiyyah al-Shalat and Risalah fi Mahiyyah al-’Ishq. The results show that although Ibn Sina was not a Sufi in the traditional sense, his thought contains traces and elements of typical philosophical mysticism, such as the doctrine of divine love, gnostic (al-arif), human connection with God (al-wushul), the doctrine of happiness, and so on. In conclusion, Ibn Sina’s system of thought is a harmonious synthesis between rationality and spirituality, between logic and intuition. Hence, these findings open a new space for dialogue between philosophy and Sufism in the Islamic intellectual tradition.